A Study on Awareness of Livestock Owners about Zoonoses in Jaipur District of Rajasthan - Meena, Jyoti; Singh Rajawat, Nirmal; Chand, Subhash; Kumar Rewani , Sanjay (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present investigation was conducted from July to November 2021 in Jaipur district of Rajasthan using an exploratory research design. The data were collected from randomly selected 120 livestock owners with the help of structured and pre-tested interview schedule. Awareness index was calculated by using weighed mean score and maximum obtainable score. Awareness of livestock owners about zoonoses was observed on five different aspects covering zoonotic diseases, their mode of transmission, animal food consumption pattern, detail information on particular zoonotic disease, their vaccination, these are which zoonotic diseases you heard, diseases of animals can transmit to man and vice versa through, animal product consumption pattern, awareness regarding various zoonotic diseases, awareness about vaccination for zoonotic diseases. The findings of study showed that majority of livestock owners had medium level of awareness for zoonotic diseases.
Keywords: Awareness; Livestock owners; Rajasthan; Risk; Zoonotic diseases